مستوى التفکیر الابداعى فى حل المشکلات لدى العاملین فى المکتبات الجامعیة بمنطقة مکة المکرمة :دراسة میدانیة - د.جیهان محمود السید (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aims to the recognition of the level of creative thinking insolving problems of academic libraries staff in Makah and determining thebarriers to its practice. It also shows how to overcome those barriers and improvetheir creative thinking; based on the importance of creative thinking in solvingproblems specifically in academic libraries since they have the responsibility ofserving researchers and contributing to the development of scientific research.The importance of this study is shown in assisting researchers and staff inacademic libraries in designing training programs for information specialists inorder to enhance their creative thinking skills in solving problems. Thedevelopment of creative thinking skills in libraries will show its effectproportionally on the performance of carried-out services. As a result, it canaccomplish as much benefits as possible from its content and services.This study utilizes field study methodology where the researcher hascollected data and facts about this topic, described, analyzed and explained themto reach a significant conclusion, using main tools for collection of data based onLikert’s scale. Likert’s method was designed to measure the level of creativethinking in solving the problems and barriers related to the process of creativethinking in these libraries. In addition to this, statistical methods have been usedto determine the relation between the variables of the study and the researchquestions.The results of the paper suggest the non-existence of any strategies forthe process of creative thinking in solving problems for staff in Saudi academiclibraries but this process is practiced singularly without planning. The results alsoshow that the level of creative thinking skills in solving problems is considered tobe medium. Moreover, the study has recognized a number of barriers that restrictthe level of creative thinking. Finally, the study proposes a number of suggestionsto overcome these problems and enhance the creative thinking skills.